2019
DOI: 10.3390/agronomy9080416
|View full text |Cite
|
Sign up to set email alerts
|

Harvesting Regimes Affect Brown Midrib Sorghum-Sudangrass and Brown Midrib Pearl Millet Forage Production and Quality

Abstract: As water levels in the Ogallala Aquifer continue to decline in the Texas High Plains, alternative forage crops that utilize less water must be identified to meet the forage demand of the livestock industry in this region. A two-year (2016 and 2017) study was conducted at West Texas A&M University Nance Ranch near Canyon, TX to evaluate the forage production and quality of brown midrib (BMR) sorghum-sudangrass (SS) (Sorghum bicolor (L.) Moench ssp. Drummondii) and BMR pearl millet (PM) (Pennisetum glaucum (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 17 publications
6
17
2
Order By: Relevance
“…However, the results for pearl millet yield in this study and those reported by Machicek et al. (2019) with 250 mm of irrigation were similar, which might be explained by similar irrigation amounts and research location.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…However, the results for pearl millet yield in this study and those reported by Machicek et al. (2019) with 250 mm of irrigation were similar, which might be explained by similar irrigation amounts and research location.…”
Section: Resultssupporting
confidence: 84%
“…Similarly, Xu, Marek, Bell, and Pietsch (2015) compared the silage yield of corn hybrids at 250 mm of irrigation. Machicek, Blaser, Darapuneni, and Rhoades (2019) compared the forage yield of BMR sorghum‐sudangrass and BMR pearl millet at 250 mm of irrigation and reported higher yield in BMR sorghum‐sudangrass. These studies have provided valuable information on the performance and yield potential of these crops in the THP.…”
Section: Introductionmentioning
confidence: 99%
“…Annuals, such as sorghum × sudangrass (SXS), offer producers more flexibility and can produce forages with increased nutritive values compared with warm‐season perennials (Tracy et al., 2010). In the case of SXS, high forage yields, 7–10 Mg ha −1 , can be produced at a time of year when TF has become semi‐dormant and is not productive (Fontaneli, Sollenberger, & Staples, 2001; Machicek, Blaser, Darapuneni, & Rhoades, 2019). However, these summer annuals are less cost‐effective (Boyer et al., 2019; Keyser, Bates, Waller, Harper, & Holcomb, 2015; Tracy et al., 2010), may not be available in early summer (Tracy et al., 2010; Zechiel, 2017) and thus provide fewer grazing days (Zechiel, 2017) than perennials.…”
Section: Introductionmentioning
confidence: 99%
“…The paper by Machicek et al [57] reports on forage yield and quality, and water use efficiency of irrigated brown midrib sorghum-sudangrass (Sorghum bicolor (L.) Moench ssp. Drummondii) and brown midrib pearl millet (Pennisetum glaucum (L.) Leeke)) under three, two, and one harvests on 30-, 45-, and 90-day intervals, respectively.…”
Section: Crop Management For Efficient Use Of Irrigation Watermentioning
confidence: 99%